Experimental Investigation on Structural Performance of Fly Ash and Ggbs Based Geopolymer Concrete - Harsha J. Abhichandani, Ranjitsing P. Gaikwad, Amruta A. Chavan, Neha S. Deshmukh (Mathematical Statistician and Engineering Applications, 2022)
The present investigation aims at studying the mechanical properties of fly ash and GGBS based geopolymer concrete. In this study, fly ash was replaced at different levels (0%, 25%, 50%, 75% and 100%) by GGBS. Sodium hydroxide (14 M) and Sodium silicate solution is used as alkaline activator in 1:1 ratio. M-25 grade of geopolymer concrete is tested for mechanical properties Viz, compressive strength, split tensile strength and flexural strength at 3,7 and 28 day and compared with normal OPC M-25 grade concrete and also the effect of ambient curing and oven curing is studied. The result shows that replacement of fly BS eliminates heat curing of geopolymer concrete. Geopolymer concrete shows better result than normal conventional concrete. Rate of gain of strength of geopolymer concrete is high at early stage however geopolymer concrete is more advantageous, economical and ecofriendly. This experimental investigation is for research purpose for strength properties of geopolymer concrete using fly ash and ground granulated furnace slag (GGBS).